FEM assessment of the effects of machining parameters in vibration assisted nano impact machining of silicon by loose abrasives. (4th May 2020) - Duong, Nick H.; Ma, Jianfeng; Lei, Shuting
In this paper, the commercial FEM software package ABAQUS 6.14/EXPLICIT is used to model a vibration assisted nano impact machining process by loose abrasives (VANILA), in which an atomic force microscope (AFM) is used as a platform and the nanoabrasives (diamond particles) injected in slurry between the workpiece (silicon) and the vibrating AFM probe impact the workpiece and result in nanoscale material removal. The FEM model is validated first and then is used to investigate the influence of impact speed, impact angle, and the frictional coefficient between the workpiece and abrasives on the nanocavity's size and depth. It is concluded that the impact speed, impact angle, and frictional coefficient between the silicon workpiece and nanoabrasives have substantial influence on the nanocavity's size and depth, the optimal size of which along with material removal rate might be achieved by simultaneously considering impact speed, impact angle, and frictional coefficient. [Submitted 20 March 2018; Accepted 23 December 2018]